AKIBAT HUKUM TERHADAP PERKAWINAN BEDA AGAMA DI INDONESIA: STUDI TERHADAP PUTUSAN PN SURABAYA NOMOR 916/PDT.P/2022/PN SBY - Patricia Karlina Dimiyati; Rosalinda Elsina Latumahina (Gapenas Publisher, 2023)
The current Marriage Law in Indonesia does not specifically explain marriages with different religious backgrounds. The absence of this regulation in Indonesia has triggered various interpretations related to the licensing of interfaith marriages. Article 2 Paragraph (1) of the Marriage Law explains that a marriage has a valid status if,